ANALYSIS OF TECHNICAL GUIDELINES FOR PRIMASERVICE IN TOURISM RESOURCES IN SERIBU ISLANDS, 2018 - Rakhmawati, Rakhmawati; Kesa, Deni Danial (Journal of Indonesian Tourism and Policy Studies, 2019)
This journal discusses the early stages, stages of implementation, and the constraints of technical service guidance activities excellent service on human resources tourism in the Seribu islands. The Seribu Islands are included into one of the KSPN (National Strategic Tourism Areas). To face the KSPN and the Asian Games will certainly be a lot of guests or tourists who come to visit the Seribu islands. Therefore, tourism industry actors, especially managers of homestays, travel agents, and tour guides in the archipelago need to conduct training activities of excellent service technical guidance to serve the upcoming tourists visiting the Seribu islands. Technical Supervision Activities Excellent Service on Human Resources Tourism is very important to improve the professionalism of tour guides, travel agents and homestay managers, provide technical knowledge and understanding of tourism insight in the Seribu islands and provide good service to the tourists.